Character Building with Students in Learning Science Approach scientific - ,, Gusmaweti (Jurnal Ipteks Terapan, 2014)
Building character, especially the younger generation of learners is very important and very urgent, if we look at the phenomena that occur and future challenges more complex. Characters such as honest, disimplin, obey the rules, responsibility, etc. are getting lost. The problems of this paper outlines "build character fantasize learners with scientific approach to learning science." Characters can be seen as a way of thinking and behaving that are typical of every individual to live, socialize, and work together in the family, community, nation, and state. The characters are well demonstrated with morals, budipekerti, and commendable behavior and become role models in the family, community, nation. Character education in school settings as learning that lead to the strengthening and development of the childs behavior as a whole is based on a certain value that is referenced by the school "which means that character education is integrated in all subjects were directed to develop the behavior of learners in their entirety. Learning the scientific approach to learning science is able to apply those values by providing exemplary, build and develop kreaktivitas willingness of learners in the learning process. Learning activities not only in the classroom, but also can be done outside the classroom and school environment with the use of information technology. Common characters such as honesty, discipline, obey the rules, or responsible, respectful, thorough, communicative, collaboration can be built through a scientific approach to the learning activities during work. It can be concluded that the learning process can build character scientifik approach learners.Keywords: , Pembelajaran , sains, character scientific, approach.